Прогнозное моделирование динамики трендов на FOREX с учетом фрактальности и рефлексивности рынка - Куссый, М.Ю. (Культура народов Причерноморья, 2004)
The methodological approach to the forecasting of dynamics of trend on FOREX with the consideration of fractality and reflexivity of market is proposed in article.